Reflections on the Body Percussion at the Municipal School Aleixo Pereira Braga II - Gomes, José Donizete Pedrosa (2016)
Why the ideas of discipline, rigidity, detachment between the educator and the educating still are so exalted in our society? Why are they still are directly associated with the learning? Are there no other ways of the learning happen and which may be more effective than this traditional models? These were the main concerns that guide us to elaborate this article. The group PET Conexão de Saberes - Música do Oprimido (Program of Tutorial Education/Connection of knowledge - Music of the Oppressed - UnB) performed in the period from 16 May to 11 July 2015 body percussion workshops at the Municipal School Aleixo Pereira Braga II (Cidade Ocidental-GO). We lived with a group of kids during the Saturdays by the morning and realized that this musical activity began a dynamic environment of learning based on the collectivity, playfulness and affectivity. The children assimilate the workshops as plays and felt free to take risks, experiment and learn about music. Thus, this experience with children of Cidade Ocidental made us reflect about the role of the affectivity in the Child Education basing ourselves in articles of Developmental Psychology area and the Social-Emotional Education.